Pengaruh Kualitas dan Layanan Website Terhadap Minat Pembelian Konsumen dalam Situs E-commerce - Nadila Rizkika Dwi Ananda Matondang; Muhammad Irwan Padli Nasution (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In the ever-growing digital era, e-commerce has become an important foundation in the world of commerce. In the midst of increasingly fierce competition, e-commerce companies are required to understand in depth the influence of website quality and service on consumer purchasing interest. This journal comprehensively investigates the impact of website quality and service in the context of e-commerce sites. Website quality, which includes appearance, performance, information, and security, as well as website services, such as customer support, payment processing, and personalization of experiences, have a significant influence on consumer perceptions and purchasing decisions. Through in-depth analysis, this journal highlights the importance of website quality and service in building strong relationships with customers, increasing retention, and achieving long-term success in the dynamic e-commerce industry. By paying attention to these factors, e-commerce companies can optimize their strategies to attract and retain consumers in this increasingly competitive environment.